Relationship between leg muscle power, stomach muscle strength, body flexibility and ankle’s coordination on side kick’s speed in Perguruan Pencak Silat Kembang Setaman Wonosobo year 2020 - Nur Hidayati; Rony Syaifullah; Singgih Hendarto (PJKR FKOR UNS, 2020)
The purpose of this research is to know the relationship between leg mucle power, stomach muscle strength, body flexibility and ankle’s coordination on side kick’s speed in perguruan pencak silat kembang setaman wonosobo year 2020. This study is a corelation researcher, it needs one meeting to collect the data. The subject of this research is 14 athletes of Kembang Setaman Wonosobo. Source of data of this research is from the athletes and the researcher. Methods of collecting data that the researcher uses are test and observation. The researcher uses SPSS to test the data. Method of data analysis that the researcher chooses is descriptive quantitative. The study used 5 variables, namely variable x with leg muscle power, abdominal muscle strength, body flexibility and ankle coordination and variable Y with side kick speed / T. Based on the results of the analysis, it can be explained that (1) leg muscle power has a significant relationship to the side kick speed / right T indicated by the sig value. 0.008 <0.05 with a contribution value of 50.5% for the right leg and a sig. 0.004 <0.05 with a contribution value of 4.1% for the left leg and a relationship between leg muscle power and the left side kick speed / T indicated by the sig value. 0.003 <0.05 with a contribution value of 2.7% for the right leg and a sig value. 0.000 <0.05, the contribution value is 66.7% for the left leg (2) the strength of the abdominal muscles is indicated by the value of sig. 0.012 and 0.047 <0.05 with a contribution value of 2% and 2.1% (3) body flexibility has no significant relationship as indicated by the sig value. 0.541 and 0.073> 0.005 (4) eye-foot coordination does not have a significant relationship as indicated by the sig value. 0.374 and0.472> 0.05. From the value of the contribution above, the contribution value is the leg muscle power compared to the abdominal muscle strength from the total value of the contribution, namely 55.6% for the side kick speed / T right and 71,1% for the contibution value for the side kick speed / T left. Based on the data above, it can be concluded from this study that there is a relationship between leg muscle power and abdominal muscle strength to side kick speed / T in the Kembang Setaman Wonosobo martial arts college in 2020 and there is no relationship between body flexibility and ankle coordination on side kick speed / T in Setaman Wonosobo Kembang Silat College 2020.